Ten prayers that changed the world : extraordinary stories of faith that shaped the course of history - Isbouts, Jean-Pierre (National Geographic, 2016)
From time immemorial, prayer has provided comfort in our darkest hours, stirred us to action beyond what we thought possible, and shown us the way through seemingly insurmountable challenges. In this engaging tour of world history, author and historian Jean-Pierre Isbouts takes us on an inspiring tour of ten prayers that played a pivotal role in world eventsu2014from the divine inspiration of Joan of Arc to Martin Luther King's powerful Prayer to Open Hearts and Minds; from George Washington's prayerful words to the newly formed American states to the horrors of Auschwitz; from Constantine the Great's prayer before battle to Gandhi's deeply moving "prayer of peace." Ten Prayers That Changed the World delves into the moments in history where faith and prayer intersected with the course of mankind.